The Practice-Based Research on Developing Online Video Advertisement within the Framework of Creative Tourism: A Case Study of the Ban Chiew Lan Hand-Woven Fabrics Group, Surat Thani Province, Thailand - Parach, Thapthep (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
Despite their cultural significance, handwoven fabrics in Thailand have seen a decline in popularity due to the rise of machine-made textiles. This research aims to support the Ban Chiew Lan Hand-Woven Fabrics Group in Surat Thani Province through promotional marketing grounded in creative tourism principles. Lacking formal expertise in branding or market communication, the community required a context-sensitive approach. Using a practice-based research methodology, the researcher engaged in field immersion, narrative listening, and creative development rooted in real-world constraints. Through interviews, situational analysis, and mind mapping, the project culminated in a short-form online video advertisement designed to resonate with Western tourists—identified as the key audience. The final video, featuring immersive storytelling, natural ambient sound, and Southern Thai music, depicts a one-day homestay experience including natural dyeing, weaving, and a visit to the scenic Chiew Lan Dam. Audience feedback guided iterative revisions, leading to added logistical information and still visuals. The completed media was adapted for multiple social media platforms. Importantly, this study synthesizes its process into a five-step Framework for Creating Community-Based Research Advertising Videos: (1) Field immersion and narrative listening, (2) Situational and marketing analysis, (3) Creative ideation, constraint mapping and semiotic strategy, (4) Prototype development and participatory review, and (5) Final production and platform adaptation. The framework demonstrates how creative storytelling, informed by real-time data, can bridge gaps between tradition, tourism, and digital communication—offering a scalable model for similar low-resource communities.